Meta-Analysis: The Effect of Problem-Based Learning in Improving Students' Critical Thinking in Vocational Education - Ridhwan Anthony; Wagino Wagino; Rahmat Desman Koto; Erzeddin Alwi; Wawan Purwanto; Donny Fernandez (Universitas Sultan Ageng Tirtayasa, 2025)
Problem-based learning (PBL) is widely recognized as an innovative teaching strategy that engages students in active learning through real-world problem-solving. This meta-analysis systematically evaluates the effectiveness of PBL in enhancing students' critical thinking abilities across vocational and technical education contexts. The study analyzed 30 research articles published between 2016 and 2024 using quantitative data from experimental and control groups. Following a rigorous five-step meta-analysis methodology, research data was collected through the Harzing's Publish or Perish program from Google Scholar, coded systematically, and analyzed using effect size calculations. Results revealed a significant positive impact of PBL on critical thinking development, with an effect size of 0.8, indicating a moderate to strong effect according to established criteria. The experimental classes implementing PBL achieved substantially higher post-test scores (mean=73.93) compared to control groups (mean=65.14). These findings demonstrate that PBL significantly enhances students' critical thinking capabilities and learning outcomes through collaborative problem-solving, active knowledge construction, and practical application of concepts. The study concludes that PBL represents an effective pedagogical approach for developing the analytical and problem-solving skills essential for vocational education graduates in today's complex professional environments.